Exploring linear algebra labs and projects with Mathematica - Arangala, Crista (Textbooks in mathematics, 2015)
Exploring Linear Algebra: Labs and Projects with Mathematica® is a hands-on lab manual for daily use in the classroom. Each lab includes exercises, theorems, and problems that guide your students on an exploration of linear algebra.